1974
DOI: 10.1111/j.1365-2133.1974.tb12458.x
|View full text |Cite
|
Sign up to set email alerts
|

Acrodermatitis enteropathica treated by zinc

Abstract: SUMMARY A case of acrodermatitis enteropathica has, after 14 years essential treatment with Diodoquin, been able to abandon this therapy on exhibition of zinc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…It can be corrected by oral zinc supplements. In untreated patients with the disease the plasma zinc concentration is usually abnormally low (Michaelsson 1974;Moynahan 1974;Portnoy and Molokhia 1974;NeIder and Hambidge 1975), but this is not a universal finding (Garretts and Molokhia 1977). Abnormally low amounts of zinc in urine (NeIder and Hambidge 1975) and hair (Amador et al 1975) have also been reported.…”
Section: Inherited Disorders Of Zinc Metabolismmentioning
confidence: 92%
“…It can be corrected by oral zinc supplements. In untreated patients with the disease the plasma zinc concentration is usually abnormally low (Michaelsson 1974;Moynahan 1974;Portnoy and Molokhia 1974;NeIder and Hambidge 1975), but this is not a universal finding (Garretts and Molokhia 1977). Abnormally low amounts of zinc in urine (NeIder and Hambidge 1975) and hair (Amador et al 1975) have also been reported.…”
Section: Inherited Disorders Of Zinc Metabolismmentioning
confidence: 92%
“…Because CQ and PBT2 appear to redistribute metals into cells, these compounds have more recently been characterized as copper and zinc ionophores. In AD, copper and zinc redistribution into deficient neurons is thought to trigger a signaling pathway that results in reduced amyloid β levels in the brain and improved cognition. , In cancers, redistribution of copper, zinc, and iron into cancer cells is thought to trigger toxic metal ion accumulation, which then results in cancer cell death. , In addition, this ionophoric character of 8HQs may explain the effectiveness of 8HQ treatment in other metal-linked diseases such as acrodermatitis enteropathica, a lethal inherited human zinc-deficiency disorder. …”
Section: Introductionmentioning
confidence: 99%
“…It was later discovered that this was a genetically determined disorder of zinc metabolism, resulting in a decreased ability to absorb zinc from the intestine (Moynahan 1974). It was then suggested that the efficacy of 5,7diiodo-8-hydroxy-quinoline might be related to the formation of an absorbable zinc-chelate (Portnoy & Molokhia 1974). Increased plasma levels of 65Zn induced by clioquinol have been shown in calves with Adema disease, which is the bovine parallel to acrodermatitis enteropathica (Flagstad 1977).…”
mentioning
confidence: 99%